PENGARUH KOMPETENSI KERJA TERHADAP KINERJA APARAT PEMERINTAH DESA (Suatu Studi Di Kecamatan Pineleng Kabupaten Minahasa) - Pandey, Juneidy; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (Sam Ratulangi University, 2015)
Abstract : This research will be based in the background by a problem in the pineleng Sub-district officeof the Regency of minahasa in the Government apparatus work competencies influence the villages thatstill have not contributed optimally. Therefore it is necessary the presence of the influence of goodworking competencies in order to improve the performance of government apparatus of the village. Thusit can be said that the Government apparatus village in the Pineleng does not yet have adequatecompetence in implementing village autonomy demands appropriate mandate Law No. 6 Year 2014 so itcan certainly will affect their performance in achieving the goals and objectives of Government and thedevelopment of the village. Based on the results of the study as already expressed above, it needs to begiven some advice, among other things: remembering the accomplishments of the Government apparatusperformance village is still low, given the still weak influence aspects of formal education andtraining/skill performance against government apparatus apparatus village, partially, only factors factorsthat influence significant working experience terhada village government apparatus performance,meanwhile, simultaneously or together, all three of these factors (education , training and workexperience) effect very significantly to the performance of the Government apparatus. Based on asummary of items 3 and 4 can be said that all the hypotheses put forward acceptable convincingly at oncehas justification of the underlying theories.Keyword : competencies, performance Government apparatus village